2022
DOI: 10.48550/arxiv.2203.10413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On monogenity of certain number fields defined by $x^{2^r}+ax^m+b$

Abstract: Let K = Q(θ) be a number field generated by a complex root θ of a monic irreducible trinomial of type F (x) = x 2 r + ax m + b ∈ Z[x] and Z K its ring of integers. In this paper, we study the monogenity of K. More precisely, when m = 1, we provide some explicit conditions on a, b, and r for which K is not monogenic. We also construct a family of irreducible trinomials which are not monogenic, but their roots generate monogenic number fields. To illustrate our results, we give some computational examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…• L. El Fadil [39] x 4 + ax + b • L. El Fadil and I. Gaál [54] x 4 + ax 2 + b • H. Smith [151] x 4 + ax + b, x 4 + cx 3 + d • L. Jones [128] showed that there exist exactly three distinct monogenic trinomials of the form x 4 + bx 2 + d with Galois C 4 • A. Jakhar, S. Kaur and S. Kumar [101] [11] x 2 r + ax m + b • H. Ben Yakkou and L. El Fadil [17] x n + ax + b, n = 5, 6, 3 k , 2 k • 3 ℓ , 2 k • 3 ℓ + 1 • A. Jakhar and S. Kumar [108] gave explicit conditions for the non-monogenity of x q s − ax − b • A. Jakhar [94] x p s − ax m − b • B. Jhorar and S. K. Khanduja [97] x n + ax + b, showed also that f ( [93] x n − ax m − b • A. Jakhar, S. Khanduja and N. Sangwan [99] x n + ax m + b • A. Jakhar, S. Khanduja and N. Sangwan [100] gave necessary and sufficient conditions in terms of a, b, m, n for a given prime p to divide I(ϑ) where ϑ is a root of x n + ax m + b • L. Jones [121] considered monogenic reciprocal trinomials of type x 2m + Ax m + 1 • L. Jones [114] showed that there are infinitely many primes p such that x 6 + px 3 + 1 is monogenic with Galois group D 6 • L. Jones [115] showed that x n + x + 1 is monogenic, if and only if its discriminant is squarefree • L. Jones and T. Phillips [130] showed that x n + ax + b is monogenic infinitely often • L. Jones and D. White [131]…”
Section: Pure Fields Trinomials Quadrinomials Etcmentioning
confidence: 99%
“…• L. El Fadil [39] x 4 + ax + b • L. El Fadil and I. Gaál [54] x 4 + ax 2 + b • H. Smith [151] x 4 + ax + b, x 4 + cx 3 + d • L. Jones [128] showed that there exist exactly three distinct monogenic trinomials of the form x 4 + bx 2 + d with Galois C 4 • A. Jakhar, S. Kaur and S. Kumar [101] [11] x 2 r + ax m + b • H. Ben Yakkou and L. El Fadil [17] x n + ax + b, n = 5, 6, 3 k , 2 k • 3 ℓ , 2 k • 3 ℓ + 1 • A. Jakhar and S. Kumar [108] gave explicit conditions for the non-monogenity of x q s − ax − b • A. Jakhar [94] x p s − ax m − b • B. Jhorar and S. K. Khanduja [97] x n + ax + b, showed also that f ( [93] x n − ax m − b • A. Jakhar, S. Khanduja and N. Sangwan [99] x n + ax m + b • A. Jakhar, S. Khanduja and N. Sangwan [100] gave necessary and sufficient conditions in terms of a, b, m, n for a given prime p to divide I(ϑ) where ϑ is a root of x n + ax m + b • L. Jones [121] considered monogenic reciprocal trinomials of type x 2m + Ax m + 1 • L. Jones [114] showed that there are infinitely many primes p such that x 6 + px 3 + 1 is monogenic with Galois group D 6 • L. Jones [115] showed that x n + x + 1 is monogenic, if and only if its discriminant is squarefree • L. Jones and T. Phillips [130] showed that x n + ax + b is monogenic infinitely often • L. Jones and D. White [131]…”
Section: Pure Fields Trinomials Quadrinomials Etcmentioning
confidence: 99%